The PCOC Symptom Assessment Scale (SAS): A valid measure for daily use at point of care and in palliative care programs - Daveson, Barbara A.; Allingham, Samuel Frederic; Clapham, Sabina; Johnson, Claire E.; Currow, David C.; Yates, Patsy; Eagar, Kathy (PloS one, 2021)
Very few measures are used successfully as part of routine care within national palliative care outcome programs. Only a handful of studies examine these measures. The aim of this study is to evaluate the validity of a measure used in a national outcomes program: the Palliative Care Outcomes Collaboration Symptom Assessment Scale (PCOC SAS). A retrospective multi-site cohort study with secondary analysis of routinely collected patient-level data to assess PCOC SAS's internal consistency, construct validity, reliability, interpretability, acceptability and sensitivity. The analyses used two sets, with data collected by inpatient and community palliative care services registered with the Australian national PCOC. Dataset one included 1,117 patients receiving palliative care from 21 services. Dataset two included 5,294 patients receiving palliative care from 119 PCOC services. PCOC SAS demonstrated the ability to detect and discriminate distress by palliative care phase, functional status and diagnosis. Excellent and good convergent and discriminant validity were demonstrated. Fair through to substantial inter-rater and intra-rater reliability levels were evidenced. Sufficient interpretability resulted along with necessary levels of acceptability and sensitivity. PCOC SAS is a valid and reliable patient-reported outcome measure suitable for use in routine clinical care with patients requiring palliative and or end-of-life care, including in national outcomes programs.